The appropriation and transformation of the landscape: the urbanization process resulting from the cultivation of the erva mate in Paraná (Brazil). Issue 2 (2nd April 2016) - Smaniotto Costa, Carlos; Rocha, Eliana do Pilar
ABSTRACT: This paper aims to describe the landscape patterns and the urbanization process which evolved due to the mate tea ( Ilex paraguariensis St. Hill ) cultivation in the Brazilian state of Paraná. Drinking mate tea is an ancient tradition of the Guarani Indians who settled the southeastern region of South America. The large-scale cultivation of mate in Paraná has been taking place for centuries, mainly in the region around the city of Irati . Mate cultivation induced the development of settlements and influenced their growth; it stamped the economic and social character of the region, and shaped a rich and characteristic landscape. As other cultural landscapes, the 'mate landscape' is undergoing changes, with agriculture and urbanization being the most important drivers. To sustain its values it is necessary to call for attention to its environmental, economic, social and cultural virtues. We discuss the ecological and aesthetic value of mate culture, and the social and environmental demands of its future. We also offer arguments and some ideas to create from the landscape a significant community added value, bearing in mind that landscape is a key element of the quality of life and an important asset for future generations.